2008
DOI: 10.1128/aem.01320-08
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Native Bradyrhizobia Isolated from Soybeans ( Glycine max L.) in Different Agricultural-Ecological-Climatic Regions of India

Abstract: Fifty isolates from root nodules of soybean plants sampled in five agricultural-ecological-climatic regions of India were analyzed by PCR-restriction fragment length polymorphism analysis of the 16S rRNA gene, the intergenic spacer region between the 16S and 23S rRNA genes (IGS), and the nifH and nodC genes. Eight haplotypes assigned to the Bradyrhizobium genus were identified, and the genetic diversity was conserved across regions. Sequence analyses of the IGS and the dnaK, glnII, recA, and nifH genes reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 28 publications
(35 reference statements)
8
68
1
Order By: Relevance
“…In another study by Satya Prakash and Annapurna (2006) also reported occurrence of soybean rhizobia that are distinct from soybean rhizobia of USA and Brazilian origin based on BOX-PCR analysis. This was further supported by occurrence of distinct rhizobia in tropical soils of India (Appunu et al 2008). Thus, remarkable differences among the rhizobial isolates observed in the current study based on C-sources utilization may have ecological significance for their exploitation in future inoculation programmes.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…In another study by Satya Prakash and Annapurna (2006) also reported occurrence of soybean rhizobia that are distinct from soybean rhizobia of USA and Brazilian origin based on BOX-PCR analysis. This was further supported by occurrence of distinct rhizobia in tropical soils of India (Appunu et al 2008). Thus, remarkable differences among the rhizobial isolates observed in the current study based on C-sources utilization may have ecological significance for their exploitation in future inoculation programmes.…”
Section: Resultssupporting
confidence: 52%
“…The genetic diversity of slow-and fast-growing rhizobia nodulating soybean was reported in many parts of the world. Recently Appunu et al (2008) studied the genetic diversity of soybean-nodulating Bradyrhizobium isolates from India and found that the diversity is wider than expected based on previous studies in various geographic areas and on the current taxonomy of soybean rhizobia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously there were reports on the isolation and characterization of B. yuanmingense strains that nodulated mungbean and soybean 9,22 and B. yuanmingense strain that did not nodulate soybean but nodulated legume species of M STB30 STB38 STB269 STB54 STB67 STB235 STB286 STB96 STB250 STB310 STB169 STB264 M bp 12,000 5,000 the genus Lespedeza 23 . In this study, two B. yuanmingense strains STB169 and STB264 were isolated.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, there are two recognized strains of fast-growing soybean rhizobia, namely Sinorhizobium fredii and S. xinjiangense 4,5 . In addition, there are 4 recognized strains of slow-growing soybean rhizobia, i.e., Bradyrhizobium elkanii, B. japonicum, B. liaoningense, and the recently-discovered B. yuanmingense biovar that nodulates soybeans [6][7][8][9] . At present, there is not much information on polyphasic taxonomy of soybean rhizobia in Thailand [10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%